The mask of the text - two works by Pepetela - Elizabeth Robin Zenkner Brose (Gragoatá, 2005)
This article analyses two novels by Pepetela: A gloriosa família - o tempo dos flamengos (The Glorious Family: the time of the flemings), and Lueji - o nascimento de um império (Lueji: the birth ofan empire). These two books are related to given periods in history: pre-colonial and colonial times and make use of different literary genres, narrators and narrative models. ln addition, they are constructed from the viewpoint of contemporary narrators who depict the daily routine of pre-colonial tribes and the intercontinental trade and transit across the Atlantic Ocean, in a manner that simulates that of the storytellers of the oral tradition. It is suggested that both novels are actually composed by narrators/translators of the dialogical plurality between the cultures and temporalities that comprise that given segment of the lusophone literary universe.